Contributions of alternative splicing to muscle type development and function. (August 2020) - Nikonova, Elena; Kao, Shao-Yen; Spletter, Maria L.
Highlights: Both vertebrates and Drosophila have diverse types of muscle fibers. Myofibers are specialized in morphology, contractility and gene isoform expression. ∼80 % of sarcomere proteins are differentially expressed or spliced in fly muscle. Splice isoforms can have specific functions in muscle development and contractility. New techniques will help evaluate isoform-specific functions in muscle. Abstract: Animals possess a wide variety of muscle types that support different kinds of movements. Different muscles have distinct locations, morphologies and contractile properties, raising the question of how muscle diversity is generated during development. Normal aging processes and muscle disorders differentially affect particular muscle types, thus understanding how muscles normally develop and are maintained provides insight into alterations in disease and senescence. As muscle structure and basic developmental mechanisms are highly conserved, many important insights into disease mechanisms in humans as well as into basic principles of muscle development have come from model organisms such as Drosophila, zebrafish and mouse. While transcriptional regulation has been characterized to play an important role in myogenesis, there is a growing recognition of the contributions of alternative splicing to myogenesis and the refinement of muscle function. Here we review our current understanding of muscle type specific alternative splicing, using examples of isoforms with distinct functions from both vertebrates and Drosophila . Future exploration of the vast potential of alternative splicing to fine-tune muscle development and function will likely uncover novel mechanisms of isoform-specific regulation and a more holistic understanding of muscle development, disease and aging.